اللبان وتأثيره الانتاجي والفسيولوجي على طائر السمان الياباني - نواره الطاهر المولدي سوف الجين; سامية الثابت هبهب; ناجية علي خليفة (Surman Journal of Science and Technology, 2024)
This study aims to determine the effect of adding frankincense at different levels on the productive performance of Japanese quail, specifically growth rate, live weight, weight gain, and feed conversion efficiency. It also aims to evaluate the effect of frankincense on the physiological characteristics of Japanese quail, including hematological and biochemical indicators related to the bird’s overall health. The study compares the statistical differences between the various treatments (5 g, 10 g, 15 g, and the control group) to determine the significance of the effect of the frankincense levels used. This study was conducted in a home aviary from 13/9/2023 to 30/10/2023 to investigate the effect of adding frankincense to the drinking water of quail. The experiment included 28 one-month-old Japanese quail raised in the aviary on the floor litter, provided with all suitable environmental conditions. Two birds died. After one week of the study, the specified quantities of frankincense powder (5, 10, and 15 grams) were weighed using a sensitive electronic scale and dissolved in one liter of clean drinking water for each treatment, with thorough stirring to ensure the homogeneity of the solution. Based on the results and the detailed discussion, the most prominent findings were drawn: a significant increase in mean weight was observed with increasing doses of frankincense, with Group D (15g) having the highest weight, statistically significant (p=0.032). Adding frankincense to drinking water, particularly at doses of 10–15g, had a clear positive effect on final weight and improved some blood parameters, especially HDL cholesterol, without causing significant negative effects on other biochemical parameters. No statistically significant differences were found between the groups (F=0.016, p=0.997), indicating that frankincense consumption did not affect total cholesterol levels. The mean was higher in Group D compared to the control group, and the difference was significant between some groups according to Tukey’s test, indicating a possible effect of frankincense on raising HDL cholesterol levels. No effect of frankincense on LDL cholesterol was found in these samples, as the mean increased with increasing dose, but the results did not reach statistical significance. The results also showed a gradual decrease in troponin levels. Troponin and creatine kinase (CKMB) levels increased with increasing doses of frankincense, potentially indicating improved cardiovascular health and muscle performance, but most differences were not statistically significant, except in some pairwise comparisons